2018
DOI: 10.1177/0954409718754927
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ballast compactness during the tamping process by using an image-based 3D discrete element method

Abstract: We investigated the dynamic behavior of a railway ballast layer during tamping operation by 3D Discrete Element simulations. The ballast layer was prepared with ballast grains that had a realistic shape and was measured by a laser scanner and modeled by clumped spheres using the dynamic optimization technique. Three types of sleeper models that were embedded in the ballast layer were prepared, and a series of tamping operations (lifting of the sleeper, insertion of vibrating tines and packing, pulling out of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A series of conventional impact compaction tests were conducted in the laboratory to obtain the optimal moisture content of UPAB materials with scaled gradations of 1–3% [ 39 ]. Previous studies revealed that the vertical stress level observed during field compaction and in-service periods is from 100 to 700 kPa [ 21 , 40 , 41 , 42 ]. The details of the orthogonal array testing along with the test design scheme are shown in Table 1 , which was obtained according to the principle of mixed-level orthogonal design.…”
Section: Experimental Materials Equipment and Testing Programmentioning
confidence: 99%
“…A series of conventional impact compaction tests were conducted in the laboratory to obtain the optimal moisture content of UPAB materials with scaled gradations of 1–3% [ 39 ]. Previous studies revealed that the vertical stress level observed during field compaction and in-service periods is from 100 to 700 kPa [ 21 , 40 , 41 , 42 ]. The details of the orthogonal array testing along with the test design scheme are shown in Table 1 , which was obtained according to the principle of mixed-level orthogonal design.…”
Section: Experimental Materials Equipment and Testing Programmentioning
confidence: 99%
“…The following column is the generation method, which describes the applied DEM software and the methods of creating the particles. The applied software includes 1) particle flow code (PFC) [82], 2) Yade [83], 3) extended discrete element method (EDEM), 4) dynamic optimization method [73], 5) BLOKS3D [84] and 6) LMGC90 [85].…”
Section: Shapementioning
confidence: 99%
“…Using the DEM models, the studies mainly concern the tamping frequency, compaction and performance after tamping, etc. [38,[67][68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Sysyn M. et al and Sysyn M. et al [30,31] allow to determine the differences in ballast compaction along the sleeper after vibration loading. Numerical simulation of ballast compaction and ballast porosity using discrete element method is shown in other papers [32][33][34][35]. Tamping operations, like sleeper lifting, tines insertion, vibrating and packing, their pulling, and sleeper settling were simulated in a realistic manner, which showed the decrease of inter-granular contacts number during the insertion of the vibrating tines and the packing process.…”
Section: Literature Reviewmentioning
confidence: 99%